PENGGUNAAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MENARIKAN TARI PUSPAWRESTHI SISWA KELAS X MIA 1 SMA N 1 BLAHBATUH KABUPATEN GIANYAR TAHUN PELAJARAN 2019/2020 - Gusti Ayu Made Puspawati (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine the use of interactive multimedia can improve responsiveness and ability to dance Puspawresthi dance students. In this classroom action research method descriptive design. The research design used in this study was classroom action research (CAR). This research was carried out through four main stages, namely (1) planning, (2) implementing actions, (3) observation and (4) reflection. The average class results obtained by students in pre-cycle of 66.97, in the first cycle increased to 71.84 and in the second cycle increased again to 80. The results of student action tests that scored above 75 in the second cycle has exceeded 75%. Classically the learning outcomes have been able to increase from 60.52% completeness in the first cycle to 100% in the second cycle. The use of interactive multimedia can improve the response of students of class X MIA 1 SMA N 1 Blahbatuh Gianyar district in the academic year 2019/2020. Judging from the first cycle, obtained an average student response results of 71, 4 with enough categories, and in the second cycle the average response of students was 84.7 with a high category. This means that the use of interactive multimedia can improve student responses in learning to improve Puspawresthi dance which is very effective and can be well received.